Denosumab Is Superior to Raloxifene in Lowering Risks of Mortality and Ischemic Stroke in Osteoporotic Women - Ting-Chun Liu; Chien-Ning Hsu; Wen-Chin Lee; Shih-Wei Wang; Chiang-Chi Huang; Yueh-Ting Lee; Chung-Ming Fu; Jin-Bor Chen; Lung-Chih Li (MDPI AG, 2023)
Both osteoporosis and cardiovascular disease (CVD) share similar pathways in pathophysiology and are intercorrelated with increased morbidity and mortality in elderly women. Although denosumab and raloxifene are the current guideline-based pharmacological treatments, their impacts on cardiovascular protection are yet to be examined. This study aimed to compare mortality rate and cardiovascular events between denosumab and raloxifene in osteoporotic women. Risks of CVD development and all-cause mortality were estimated using Cox proportional hazard regression. A total of 7972 (3986 in each group) women were recruited between January 2003 and December 2018. No significant difference between denosumab and raloxifene was observed in composite CVDs, myocardial infarction, or congestive heart failure. However, comparison of the propensity score matched cohorts revealed that patients with proportion of days covered (PDC) ≥60% had lower incidence of ischemic stroke in the denosumab group than that in the raloxifene group (aHR 0.68; 95% CI 0.47-0.98; p = 0.0399). In addition, all-cause mortality was lower in the denosumab group than in the raloxifene group (aHR 0.59; 95% CI 0.48-0.72; p = 0.001), except in patients aged <65 y/o in this cohort study. We concluded that denosumab is superior to raloxifene in lowering risks of all-cause mortality and certain ischemic strokes in osteoporotic women.